Metacognitive, Cognitive, and Socio-Affective Strategies Used By English First Language Students in Academic Listening Course - Sweethsy Awinindia (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2023)
Listening has an essential role in the language learning process. The success or failure of language learning is influenced by how students use the strategies. However, sometimes students still find it difficult to choose appropriate listening strategies. Therefore, listening strategies are crucial for the learning process in English as a foreign language context. This study aimed to investigate the learning strategies used by the English Language Education Program students in the Academic Listening course. The study was conducted in the first semester, 2022/2023 academic year. By using qualitative methods, the researchers employed close-ended and open-ended questionnaires and semi-structured interview protocols to collect the data. The participants were thirty seven students of batch 2021 who have taken the Academic Listening course. The findings showed that the students used metacognitive, cognitive, and socio-affective strategies. In metacognitive, they tended to make plans before study, paid attention to the speakers, and learned from previous mistakes. Students also used dictionaries and glossaries to define the meaning of unfamiliar words, took notes, and summarized cognitive strategies. Then, they tended to relax and practiced English with others in socio-affective strategies. The study hopefully can increase Academic Listening students' awareness of listening strategies that can help them during the learning process. Moreover, it is hoped to be useful for lecturers who want to teach Academic Listening and support students’ listening strategies.